Supervisory Sharia Board, Leverage, and Firm Value: ISR's Mediating Role in IDX Financial Issuers - Nisa Anafiyah; Datien Eriska Utami (Journal of Economics and Management Scienties, 2026)
Investor interest in enterprises operating under sharia law has grown in tandem with the rapid expansion of the sharia capital market. Companies are competing to have a corporate image based on sharia principles. The purpose of this study is to understand the contribution of the Sharia Supervisory Board (SSB), leverage, and Islamic Social Reporting (ISR) disclosure in increasing firm value in the sharia, and to examine the role of ISR as a key mediating factor in these relationships. This study employs an explanatory method to test the theory objectively, utilizing a quantitative approach with a path analysis test. It uses secondary data obtained from the IDX stock list as well as annual reports and sustainability reports. The sampling technique used in this study is purposive sampling. The SSB and leverage variables have a positive and significant effect on Islamic Social Reporting (ISR). This finding supports signaling theory, where companies with larger SSB and high leverage tend to increase Islamic social transparency to reduce information asymmetry with stakeholders. The intervening variable ISR does not have a significant effect on the dependent variable, namely, firm value. The test results show that the intervening variable, ISR, also cannot mediate the relationship between the DPS and leverage variables with firm value. However, ISR and SSB as intervening variables to mediate the effect on firm value highlights the limitations of linear mediation models in the context of Islamic finance, so that the development of a theory that integrates sharia governance metrics into the national sustainable development framework is needed.